Analisis Pengendalian Kualitas Guna Meminimalsir Deffect Dengan Pendekatan Metode Statistical Quality Control (SQC) (Studi Kasus di PT. Romi Violeta Sidoarjo) - Akhmad Fatikul Azzam; Setijanen Djoko Harijanto (Jurnal Kendali Teknik dan Sains, 2023)
PT Romi Violeta Sidoarjo is one of the furniture companies in Indonesia, specializing in rattan and wood products, offering them to the global market. Quality is also a key factor for the company, as good quality is considered an achievement. In the production process, there are inevitably product errors that do not meet specifications or defects, one of which occurs during the finishing process, where there are 8 types of defects. In the data of the quality control department for finishing in the year 2022, there were 246 instances of defects out of a total production of 10,921. This can hinder further production processes, and the company will incur losses due to costs and expenses for repairing defective products. The research is conducted with the aim of determining the level of product quality control, the causes of product defects, and preventive actions or improvement proposals to reduce the defect rate. The method used in this research is Statistical Process Control (SPC), which aims to minimize the defect rate. From the calculations and analysis of the Statistical Process Control (SPC) results for the eight types of defects, the dominant defect type is color variation, which accounts for 67 instances with a percentage of 27.2%. Furthermore, on the control chart calculations, findings were made for the data samples in January, June, August, and September. The cause-and-effect diagram revealed factors such as human, machine, raw materials, methods, and the environment that can contribute to defects. However, the largest cause is human error, as almost 90% of the finishing work is done by humans, often without following the Standard Operating Procedures (SOP) set by the company.